2020
DOI: 10.21037/tcr-20-686
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a potential microRNA, transcription factor and mRNA regulatory network in hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide and the third leading cause of cancer-related death. MicroRNAs and transcription factors (TFs) cooperate to regulate the same target gene, thus affecting the progression of HCC.Methods: Differentially expressed miRNAs and mRNAs were screened. Functional enrichment analysis of these HCC-related mRNAs was performed, and a protein-protein interaction network was constructed. TFs that regulate these miRNAs and hub genes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Furthermore, they found that increased expression of CCNF mRNA was associated with worse OS, relapse free survival (RFS), distant metastasis free survival (DMFS), and post progression survival (PPS), and further demonstrated the elevated levels of cyclin F protein in BC tissues using IHC [ 15 ]. Similar studies of Wang et al [ 16 ] have also revealed that high mRNA expression levels of CCNF denote a poor prognosis in BC patients, whereas Li et al [ 17 ] have reported corresponding findings for hepatocellular carcinoma (HCC). Conversely, CCNF mRNA levels correlated with better survival outcome in colorectal cancer (CRC), as it has been presented by Chen et al [ 18 ] based on the in silico analysis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, they found that increased expression of CCNF mRNA was associated with worse OS, relapse free survival (RFS), distant metastasis free survival (DMFS), and post progression survival (PPS), and further demonstrated the elevated levels of cyclin F protein in BC tissues using IHC [ 15 ]. Similar studies of Wang et al [ 16 ] have also revealed that high mRNA expression levels of CCNF denote a poor prognosis in BC patients, whereas Li et al [ 17 ] have reported corresponding findings for hepatocellular carcinoma (HCC). Conversely, CCNF mRNA levels correlated with better survival outcome in colorectal cancer (CRC), as it has been presented by Chen et al [ 18 ] based on the in silico analysis.…”
Section: Discussionsupporting
confidence: 54%
“…Conversely, CCNF mRNA levels correlated with better survival outcome in colorectal cancer (CRC), as it has been presented by Chen et al [ 18 ] based on the in silico analysis. In contrast to the study by Li et al [ 17 ], Fu et al [ 19 ] have provided evidence for high expression of cyclin F mRNA and protein being correlated with better survival of HCC patients. Here, we also observed that patients with tumors that express more cyclin F protein survived longer than those with its low expression, though our results were not statistically significant (606 days vs. 314 days; p = 0.14).…”
Section: Discussionmentioning
confidence: 68%
“…Since miRNAs are strictly regulated by different transcription factors, altered expression of miRNAs in cancer may be caused by dysregulation of some transcription factors, such as c-Myc and p53 [ 48 ]. The proto-oncogene c-Myc plays a fundamental regulatory role in growth control, cell proliferation, differentiation, and apoptosis, and alterations in its expression are associated with many tumors.…”
Section: Mirnas In Cancermentioning
confidence: 99%
“… Ouimet et al (2016) reported that induction of miR-33 inhibited autophagy and lipid catabolism, promoted M. tuberculosis replication, and led to the bacteria survival in host cells. In addition, Lin et al (2017) demonstrated that multiple miRNAs could simultaneously interact with the transcription factor CEBPB to regulate the expression of FCGR1A, a gene associated with TB, which in turn affects TB development. Increasing evidence in recent years has also shown that M. tuberculosis has evolved various strategies to impair host autophagy mechanisms.…”
Section: Introductionmentioning
confidence: 99%